KMT2D regulates activation, localization, and integrin expression by T-cells - Potter, Sarah J.; Zhang, Li; Kotliar, Michael; Wu, Yuehong; Schafer, Caitlin; Stefan, Kurtis; Boukas, Leandros; Qu’d, Dima; Bodamer, Olaf; Simpson, Brittany N.; Barski, Artem; Lindsley, Andrew W.; et al. (Frontiers in Immunology, 2024)
Individuals with Kabuki syndrome present with immunodeficiency; however, how pathogenic variants in the gene encoding the histone-modifying enzyme lysine methyltransferase 2D (KMT2D) lead to immune alterations remain poorly understood. Following up on our prior report of KMT2D-altered integrin expression in B-cells, we performed targeted analyses of KMT2D’s influence on integrin expression in T-cells throughout development (thymocytes through peripheral T-cells) in murine cells with constitutive- and conditional-targeted Kmt2d deletion. Using high-throughput RNA-sequencing and flow cytometry, we reveal decreased expression (both at the transcriptional and translational levels) of a cluster of leukocyte-specific integrins, which perturb aspects of T-cell activation, maturation, adhesion/localization, and effector function. H3K4me3 ChIP-PCR suggests that these evolutionary similar integrins are under direct control of KMT2D. KMT2D loss also alters multiple downstream programming/signaling pathways, including integrin-based localization, which can influence T-cell populations. We further demonstrated that KMT2D deficiency is associated with the accumulation of murine CD8+ single-positive (SP) thymocytes and shifts in both human and murine peripheral T-cell populations, including the reduction of the CD4+ recent thymic emigrant (RTE) population. Together, these data show that the targeted loss of Kmt2d in the T-cell lineage recapitulates several distinct features of Kabuki syndrome-associated immune deficiency and implicates epigenetic mechanisms in the regulation of integrin signaling.